Biodegradability of cellulose nanocrystal/thermoplastic polyurethane nanocomposite - Afkar Rabbani Hidayatullah, Hipeni; Intan Syahiera, Azli; Khairatun Najwa, Mohd Amin (2021)
The novelty of this research is the application of CNC from filter paper as filler to improve the properties of thermoplastic polyurethane and enhance the biodegradability of nanocomposites.